Assessment of Knowledge, Attitude, and Practice about Hepatitis B among Patient Porters of the Training and Treatment Hospitals of Rafsanjan, 2011: - bidaki, Reza; Asadpour, Mohammad; Arabbaniassad, Fatemeh; Moazzeni, Vida; Shabani, Ziba; Sayadi, Ahmadreza (Galen Medical Journal, 2013)
Introduction: Hepatitis B is a viral infection that is potentially life-threatening and is transmitted through contact with the blood or other body fluids of an infected one. Hepatitis B is, therefore, an important professional hazard for health care workers. This aim of this study was to assess the practical knowledge of hepatitis B among the patient porters of the training and treatment hospitals of Rafsanjan. Material and Methods: This descriptive study is a crosssectional study utilizing a self-made questionnaire comprised of four sections on demographic information, attitude towards hepatitis B, knowledge of hepatitis B, and practical measures against hepatitis B. Face and content validity and reliability of the questionnaire was performed. After the completion of the questionnaire, parametric and non-parametric tests were conducted to assess the relationship between the study variables. A P value <0.05 was considered statistically significant. Results: In this study, 86 individuals filled the questionnaires (response rate =86%). Results showed that the most prevalent age was between 31 and 40 years old (60%), the dominant sex was male (62.4%), the majority had more than ten years of work experience (64.5%), and a high percentage had a middle school educational level (45.9%). Our results also showed that the majority of the respondents had received training about hepatitis B, and there was no significant relation between some demographic information such as work place and educational level and knowledge, attitude, and practice about hepatitis B. Conclusion: The degree of knowledge, attitude, and practice in regard to hepatitis B among the patient porters of the training and treatment hospitals of Rafsanjan was favorable. [GMJ. 2012;1(2):60-65]